MARGARET CROCKETT, The No-Nonsense Guide to Archives and Recordkeeping - Serran, Jamie (Archivaria, 2016)
The No-Nonsense Guide to Archives and Recordkeeping. MARGARET CROCKETT. London: Facet Publishing, 2016. xi, 212 pp. ISBN 1-85604-855-2.